Case report of intestinal pseudo obstruction: a rare presentation of hypothyroidism - Nikshoar , Mohammadreza; Anaraki, Fakhr-o-sadat; Haj Mohamad Ebrahim Ketabforoush, Arsh; Parhizgar, Parynaz; Tavallaei, Mehdi (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: It is now well known that thyroid disorders can affect the structure and function of the gastrointestinal tract. Hypothyroidism is associated with a wide range of intestinal symptoms, including constipation, bloating, flatulence, atrophic gastritis, ileus, atony, and dilatation of the esophagus stomach, gallbladder, small intestine, and colon. In uncontrolled and severe cases, the disease can lead to intestinal pseudo obstruction, paralytic ileus, and megacolon. In this case report, we presented a patient suffering from intestinal pseudo obstruction secondary to severe hypothyroidism. Case Presentation: The patient was an 83-year-old woman who was hospitalized due to abdominal pain. The patient had uncontrolled hypothyroidism and complained of intestinal obstruction with the main symptom of no gas and fecal excretion. Abdominal CT scan shows dilated small and large bowel down to the rectum especially more dilated rectum, more suggestive of bowel ileus without mechanical obstruction. With the proper replacement of thyroid hormones, the patient’s obstruction was resolved and she was discharged from the hospital in good general condition. Conclusions: Since hypothyroidism can rarely lead to intestinal pseudo obstruction, we recommend that hypothyroidism be considered as an underlying cause in patients with uncontrolled hypothyroidism and obstruction of the small intestine without any mechanical obstruction.